ARTISTIC DISCUSSION OF THE SUBJECT MATTER OF THE KATHOTIA ROCK PAINTINGS: कठोतिया के शैलचित्रों की विषय वस्तु का कलात्मक विवेचन - Pandey, Anjali; Mishra, Anjali (International Journal of Research -GRANTHAALAYAH, 2017)
Adi Man first embodied his thoughts and experiences through art. Through illustrating images of inner feelings and imaginations, he pioneered an innovative tradition that probably lasts forever. The sculptures drawn by human beings not only have knowledge of the true nature of the Tadugin culture, along with it they also show the creativity, creativity and artistic aptitude of the human. आदि मानव ने अपने विचारों एवं अनुभूतियों को सर्वप्रथम कला के द्वारा मूर्त रूप प्रदान किया। अंतस् के भावों एवं कल्पनाओं की चित्रों के माध्यम से व्यंजना कर उसने संभवतः चिर्काल तक अक्षुण्ण रहने वाली अभिनव परम्परा का सूत्रपात किया। पुरा मानव द्वारा आरेखित शैलचित्रों द्वारा तद्युगीन संस्कृति के यथार्थ स्वरूप का ज्ञान तो होता ही है, इसके साथ ही इनसे आदि मानव की सृजनात्मकता, रचनाशीलता व कलात्मक अभिवृत्ति का भी द्योतन होता है।